Treatment Strategy for Unexplained Infertility and Recurrent Miscarriage (Springer Singapore, 2018)
This book offers a highly informative guide to treating unexplained infertility and recurrent miscarriage (RM). In particular, it provides detailed treatment strategies for infertility or RM derived from uterine circumstance such as chronic endometritis and perturbation of endometrial decidualization, as well as maternal immunological rejection of an embryo as semi-allograft. Unexplained infertility refers to those types that cannot be detected by the general screening test. The causes are sometimes detected in the course of treatment with assisted reproductive technology including IVF. However, some unexplained infertility is intractable even after intracytoplasmic sperm injection or repeated implantation of morphologically suitable embryos. Patients with unexplained RM also have a high likelihood of undetectable risk factors of miscarriage. As a result, gynecologists often repeatedly provide these couples with general treatments for infertility and miscarriage or even discontinue treatment because they cannot detect the reason, which places serious financial, physical and mental burdens on the couples affected. This book offers gynecologists essential insights into the pathological condition of unexplained infertility and RM, equipping them to identify it, explain it to patients, and consider further examinations and more aggressive fertility treatments.